Relationship between team climate and satisfaction at work in the Family Health Strategy - Marina Peduzzi; Heloise Lima Fernandes Agreli; Pilar Espinoza; Mitti Ayako Hara Koyama; Everson Meireles; Patrícia Campos Pavan Baptista; Michael West (Universidade de São Paulo, 2022)
ABSTRACT OBJECTIVE To analyze the association between team climate, team characteristics and satisfaction at work in teams of the Estratégia Saúde da Família com Saúde Bucal (Family Health Strategy with Oral Health) (ESF with SB). METHODS Cross-sectional correlational study with ESF teams with SB in the municipality of São Paulo. Universe of 1,328 teams and random sample of 124 teams with 1,231 professionals. Applied questionnaire with data teams' characterization, team climate scale, and satisfaction at work. Analysis of validity, of climate and satisfaction scores through mean among professionals in each team, cluster analysis, association between variables by Pearson's correlation and Chi-square, and tested linear regression model for the two factors of satisfaction at work. RESULTS There was a directly proportional association between team climate and satisfaction at work. The better the climate with regard to team goals, the greater the intrinsic satisfaction at work and with the physical environment. The better the climate with regard to team goals and task orientation, the greater the satisfaction with hierarchical relations. The group with best team climate reported higher percentage of teams ranked with better satisfaction at work, and in the group with the worst team climate there was higher percentage of teams with the lowest satisfaction at work. CONCLUSIONS The study provides consistent although moderate evidence of association between favorable teamwork climate and job satisfaction in ESF with SB. It emphasizes the dimensions of climate, common goals and task orientation, and may serve as subsidy for management and permanent education of teams, aiming at the quality of care to the health needs of users, family and community in APS.